Avaliação microbiológica de queijo de coalho misto de vaca e cabra - Soares, Luana Dayana Silva (Universidade Federal Rural do Semi-Árido, 2021)
Due to the small number of studies evaluating the microbiological quality of the coalho cheese mixed with goat and cow's milk, the objective was to verify the behavior of different microorganisms in this product, with an emphasis on the use of good manufacturing practices. For this, three types of mixed rennet cheeses were produced with proportions of 25%-75%, 50%-50% and 75%-25% of goat and cow's milk, respectively. The samples were evaluated for the presence of: mesophilic, psychotrophic, coagulase positive staphylococci, Salmonella sp. and total and thermotolerant coliforms. The analyzed cheeses were suitable for Salmonella sp. showing absence in the three treatments. For the other analyses, the analyzed treatments showed high microbiological contamination, being outside the standards required for commercialization. The use of different proportions of goat and bovine milk did not generate distinct microbiological results, so they can be used to enhance the goat product and better accept the consumer public. It is essential to emphasize the importance of hygiene and good practices when producing food of animal origin, seeking food safety.
Keywords: Derivado Lácteo; Análise microbiológica.; Boas práticas de fabricação; Queijo de coalho; Milky Derivative; Microbiological analysis; Good manufacturing practices; Curd cheese; CIENCIAS AGRARIAS::ZOOTECNIA